2016
DOI: 10.1016/j.heares.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of the cochlear intrastrial fluid-blood barrier (review)

Abstract: The blood-labyrinth barrier (BLB) in the stria vascularis is a highly specialized capillary network that controls exchanges between blood and the intrastitial space in the cochlea. The barrier shields the inner ear from blood-born toxic substances and selectively passes ions, fluids, and nutrients to the cochlea, playing an essential role in the maintenance of cochlear homeostasis. Anatomically, the BLB is comprised of endothelial cells (ECs) in the strial microvasculature, elaborated tight and adherens juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
173
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 169 publications
1
173
0
3
Order By: Relevance
“…For example, human temporal bone studies of hearing loss in Sjogren's syndrome revealed immunoglobulin G deposition in the basement membrane of the stria vascularis [16]. Disrupted vascular integrity in the stria vascularis changes the blood barrier permeability in the stria vascularis [15]. In our case, noncontrast FLAIR revealed high signal intensity in the whole cochlea and vestibule (Figure 1), which might reflect an increased concentration of protein passing through blood vessels with increased permeability [17].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, human temporal bone studies of hearing loss in Sjogren's syndrome revealed immunoglobulin G deposition in the basement membrane of the stria vascularis [16]. Disrupted vascular integrity in the stria vascularis changes the blood barrier permeability in the stria vascularis [15]. In our case, noncontrast FLAIR revealed high signal intensity in the whole cochlea and vestibule (Figure 1), which might reflect an increased concentration of protein passing through blood vessels with increased permeability [17].…”
Section: Discussionmentioning
confidence: 57%
“…Circulating immune complexes have been reported in cases of SNHL associated with TAK [5,14]. There is evidence suggesting that strial capillaries may be a target of autoimmune hearing disorders [15]. For example, human temporal bone studies of hearing loss in Sjogren's syndrome revealed immunoglobulin G deposition in the basement membrane of the stria vascularis [16].…”
Section: Discussionmentioning
confidence: 99%
“…The physical blood-tissue barrier is comprised of ECs in the strial microvasculature, elaborated tight and adherens junctions, and accessory cells such as PCs, basement membrane (BM), and PVM/Ms, which together form a complex blood-tissue barrier with region-specific features(Shi, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The BLB divides the vascular compartment of the inner ear from the inner ear fluid spaces. The BLB consists of a network of vascular endothelial cells coupled together by tight junctions, basement membrane, pericytes, and perivascular resident macrophage‐like melanocytes that, combined, regulate exchange between the blood and surrounding perivascular space . In addition to maintaining normal fluid and ion physiology and preventing pathogens from entering the inner ear, the BLB also prevents therapeutic agents in systemic circulation from accessing the inner ear.…”
Section: Anatomic Barriersmentioning
confidence: 99%